Pengelolaan Potensi Pariwisata Alam Kabupaten Pekalongan Tahum 2012-2015 - Kodrat Alam; Sulistyowati . (Journal of Politic and Government Studies, 2017)
MANAGEMENT OF POTENTIAL NATURE TOURISM PEKALONGAN REGENCY YEAR 2012-2015 AbstractTourism is a service industry that is used as one of the sectors that can increase revenue domestic income. Pekalongan regency has the potential of tourism, especially eco-tourism. Location Regency Pekalongan near the northern coast line makes it easy to reach at the same time directly adjacent to the Java Sea and the mountain range makes this district has a natural charm of beaches and beautiful mountains. In this regard it is necessary to good tourism management of Youth, Sport and Tourism Pekalongan.This type of research is descriptive qualitative analytical approach, which is intended to present an overview of the situation or phenomenon in the study in detail. Source of data derived from primary data and secondary data. Determination of informants by using purposive sampling relevant Department and several locations of tourist destinations. The collection of data, researchers used three (3) methods, the method of interview, observation and document study. The number of existing attractions strategy requires the development of the tourism potential of all stakeholders such as government, private sector and share of the local community.The study found that Pekalongan has many natural tourism potential in Pekalongan. Barriers are found in tourism management include the limited facilities and infrastructure and the lack of cooperation involving the public and private sector to develop nature tourism potential in Pekalongan Regency. Keywords: Management, Cooperation and Tourism